Combining ray tracing with device modeling to evaluate experiments for an optical analysis of crystalline Si solar cells and modules. (September 2017) - Yang, Yang; Liu, Ruimin; McIntosh, Keith R.; Abbott, Malcolm; Sudbury, Ben; Holovsky, Jakub; Ye, Feng; Deng, Weiwei; Feng, Zhiqiang; Verlinden, Pierre J.; Altermatt, Pietro P.
Abstract: This paper develops a procedure to analyse the optical losses of both crystalline Si cells in air and of modules in an industrial environment. We evaluate EQE and reflectance (R) measurements on the cell, and R measurements on various spots of the module by combining the recently developed module ray tracer from PV Lighthouse with established Sentaurus device modeling. The IQE is the product of absorptance (Aeh ) in Si due to e-h pair generation and their collection efficiency (ηcol ). With Sentaurus device modeling of our PERC cells, we can model ηcol to high precision and compute Aeh from the IQE. At long wavelengths, this Aeh allows us to quantify light trapping in both the cell in air and the cell in the module without fitting internal reflectance etc. At short wavelengths, the parasitic absorptance Apar in the front SiNx layer is precisely evaluated with ellipsometry, photothermal deflection spectroscopy (PDS), and ray tracing. In the module, we reproduce the R measurements with the ray tracer and obtain R at the backsheet and the ribbon by iteration and evaluate their Lambertian factor by consistency. The ray tracing model, based on these measurements and with the achieved consistencies, then gives us an optical loss analysis of all parts of the cell and the module and allows us to evaluate possible improvements to high precision.